SUFISME DALAM SYAIR HAMZAH FANSURI - Haryadi Haryadi (LITERA, 2012)
This study aims to reveal the divine vision, worldly vision, and concept of makingthe self close to God according to Hamzah Fansuri. The data sources were Syair Perahu I and Syair Perahu II transcribed by Braginsky. The data were collected through repeated reading. They were analyzed using the qualitative descriptive technique with a reference to literary and sufism theories. The study reveals three conclusions. First, according to Hamzah Fansuri, human beings’ closeness to God can reach the highest level, namely the unification of the creature and the creator. Second, Hamzah Fansuri views the world as something temporary and the life after as something eternal. Third, Hamzah Fansuri’s concept of making the self close to God includes (a) being aware of the self, (b) remembering God and expressing praises, (c) performing good deeds, (d) controlling the passion and living simple life, and (e) avoiding evil deeds.